The Relationship Between The Level Of Knowledge About FE Tablets For Pregnant Women And Compliance With Taking FE Tablets In The Kampung Delima Health Center Working Area In 2024 - Sulaika, Belkis; Rossita, Taufanie; Sari, Liya Lugita (Universitas Dehasen Bengkulu, 2025)
Data obtained from the Rejang Lebong District Health Office in 2023 obtained the number of pregnant women in the Rejang Lebong District area as many as 5,437 pregnant women, with 857 anemic pregnant women (46.5%). Of the 21 health centers in Rejang Lebong Regency, 125 (6.9%) pregnant women with anemia were found in Kampung Delima health center. This figure is considered still high for the incidence in one health center. This study aims to determine the relationship between the level of knowledge about Fe tablets and the compliance of Fe tablet consumption among pregnant women in the working area of Puskesmas Kampung Delima. The research design used in this thesis is quantitative research with a cross-sectional approach. The population used in this study were pregnant women in the month with a gestational age of 28-33 weeks who did Antenatal Care at Puskemas Kampung Delima in June 2024 totaling 40 pregnant women. The research instruments used in this thesis are questionnaires and cheklists. The results of this study found that the initial hypothesis of the study was accepted and H0 was rejected, namely that there was a significant relationship between the knowledge and attitudes of pregnant women at Puskesmas Kampung Delima towards compliance with Fe tablet consumption with a p value from the Chi Square test results of 0.0001 which is smaller than the reference value of 0.05.